2009
DOI: 10.1515/znc-2009-9-1009
|View full text |Cite
|
Sign up to set email alerts
|

Free Phenolic Acids from the Seaweed Halimeda monile with Antioxidant Effect Protecting against Liver Injury

Abstract: Phenolic compounds are found in seaweed species together with other substances presenting antioxidant activity. The objective of this work was to evaluate the antioxidant activity of the free phenolic acids (FPA) fraction from the seaweed Halimeda monile, and its activity to protect the expression of hepatic enzymes in rats, under experimental CCl4 injury. The antioxidant activity was measured by the DPPH method. The FPA fraction (80 mg/kg, p.o.) was administered during 20 consecutive days to rats. The peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 19 publications
2
26
0
Order By: Relevance
“…Direct antioxidants that have the function of eliminating formed free radicals before they can start a specific damage, and this is done with endogenous antioxidant biomolecules located in the cell membrane and in the cytosol or exogenous compounds provided by the diet. Halimeda spp extracts exhibited a high free radical scavenging activity which could be explained by its polyphenolic compounds content [7][8][9][10][11][12][13][14][15]21].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Direct antioxidants that have the function of eliminating formed free radicals before they can start a specific damage, and this is done with endogenous antioxidant biomolecules located in the cell membrane and in the cytosol or exogenous compounds provided by the diet. Halimeda spp extracts exhibited a high free radical scavenging activity which could be explained by its polyphenolic compounds content [7][8][9][10][11][12][13][14][15]21].…”
mentioning
confidence: 99%
“…We observed that the treatment with the seaweed Halimeda spp led to a significant increase in the activity of these enzymes, which in turn resulted in an enhanced antioxidant defense. Mancini-Filho et al [12] reported an over-expression of catalase genes by treatment with FPA from Halimeda monile, while de Oliveira e Silva et al [14] by RT/PCR analysis showed an increase in the catalase gene expression in the group treated with free phenolic acid (FPA) fractions from Halimeda opuntia, suggesting the inductor effect of these compounds on the enzyme genes. Accordingly, Vidal et al [21] demonstrated similar effect with Halimeda incrassata.…”
mentioning
confidence: 99%
See 3 more Smart Citations